Use of Scheimpflug imaging in the management of intra-lenticular foreign body - Singh, R; Ram, J; Gupta, R (Nepalese Journal of Ophthalmology, 2015)
Introduction: Asymptomatic traumatic intra-lenticular foreign body is very uncommon and few case reports have been published.Objective: To report a case of post-traumatic intra-lenticular foreign body and use of Scheimpflug imaging in its management. Case: A 41-year-old male with history of injury to right eye during hammering a chisel 1 year back presented with decreased vision since 6 months. An intra-lenticular foreign body was found on slit lamp bio-microscopy and was confrmed by Scheimpflug imaging. Posterior capsule was intact on Scheimpflug imaging. Thus, Scheimpflug imaging helps in exact localization of the foreign body in the intralenticular space or behind the iris. We ruled out other foreign bodies by x-ray and ultrasonography of the orbit. The foreign body with post-traumatic cataract was removed using phacoemulsification and three piece foldable intraocular lens was implanted in the bag. Conclusion: An intra- lenticular foreign body may remain asymptomatic for months. Scheimpflug imaging can be useful in its localization. It can be removed during phacoemulsification.